Review on Microreactors for Photo-Electrocatalysis Artificial Photosynthesis Regeneration of Coenzymes - Liu, Haixia; Sun, Rui; Yang, Yujing; Zhang, Chuanhao; Zhao, Gaozhen; Zhang, Kaihuan; Liang, Lijuan; Huang, Xiaowen (Micromachines (Basel), 2024)
In recent years, with the outbreak of the global energy crisis, renewable solar energy has become a focal point of research. However, the utilization efficiency of natural photosynthesis (NPS) is only about 1%. Inspired by NPS, artificial photosynthesis (APS) was developed and utilized in applications such as the regeneration of coenzymes. APS for coenzyme regeneration can overcome the problem of high energy consumption in comparison to electrocatalytic methods. Microreactors represent a promising technology. Compared with the conventional system, it has the advantages of a large specific surface area, the fast diffusion of small molecules, and high efficiency. Introducing microreactors can lead to more efficient, economical, and environmentally friendly coenzyme regeneration in artificial photosynthesis. This review begins with a brief introduction of APS and microreactors, and then summarizes research on traditional electrocatalytic coenzyme regeneration, as well as photocatalytic and photo-electrocatalysis coenzyme regeneration by APS, all based on microreactors, and compares them with the corresponding conventional system. Finally, it looks forward to the promising prospects of this technology.